Design and evaluation of an incoherent feed-forward loop for an arsenic biosensor based on standard iGEM parts. Issue 1 (8th December 2017) - Barone, Federico; Dorr, Francisco; Marasco, Luciano E; Mildiner, Sebastián; Patop, Inés L; Sosa, Santiago; Vattino, Lucas G; Vignale, Federico A; Altszyler, Edgar; Basanta, Benjamin; Carlotto, Nicolás; Gasulla, Javier; et al.
Abstract: The diversity and flexibility of life offers a wide variety of molecules and systems useful for biosensing. A biosensor device should be robust, specific and reliable. Inorganic arsenic is a highly toxic water contaminant with worldwide distribution that poses a threat to public health. With the goal of developing an arsenic biosensor, we designed an incoherent feed-forward loop (I-FFL) genetic circuit to correlate its output pulse with the input signal in a relatively time-independent manner. The system was conceived exclusively based on the available BioBricks in the iGEM Registry of Standard Biological Parts. The expected behavior in silico was achieved; upon arsenic addition, the system generates a short-delayed reporter protein pulse that is dose dependent to the contaminant levels. This work is an example of the power and variety of the iGEM Registry of Standard Biological Parts, which can be reused in different sophisticated system designs like I-FFLs. Besides the scientific results, one of the main impacts of this synthetic biology project is the influence it had on team's members training and career choices which are summarized at the end of this article.